2019
DOI: 10.3389/fpsyt.2019.00372
|View full text |Cite
|
Sign up to set email alerts
|

Physician View and Experience of the Diagnosis of Autism Spectrum Disorder in Young Children

Abstract: Introduction: Clinicians working with children with autism spectrum disorder (ASD) occupy an important position between parents and the wide-ranging research findings. However, it is not widely known how clinicians view and experience ASD in children, even though their perspective has been shown to significantly influence their work. Material and methods: Sixteen physicians working with preschool children without a diagnosis of (intellectual or other) disability with a (presu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…This might be because most physicians in primary health care are not experienced in diagnosing ASD. This finding was supported by previous studies that reported that ASD is difficult to define, diagnose, and the physicians cannot translate their theoretical knowledge of ASD into their clinical practice, which shows a lack of experience in ASD diagnosis in primary health care physicians [ 22 , 23 ]. To overcome this, a previous study suggested a valid scale easily performed by any healthcare provider and does not require special training which might be distributed to primary health care and even to educators [ 5 ].…”
Section: Discussionsupporting
confidence: 79%
“…This might be because most physicians in primary health care are not experienced in diagnosing ASD. This finding was supported by previous studies that reported that ASD is difficult to define, diagnose, and the physicians cannot translate their theoretical knowledge of ASD into their clinical practice, which shows a lack of experience in ASD diagnosis in primary health care physicians [ 22 , 23 ]. To overcome this, a previous study suggested a valid scale easily performed by any healthcare provider and does not require special training which might be distributed to primary health care and even to educators [ 5 ].…”
Section: Discussionsupporting
confidence: 79%
“…Later on in the diagnostic trajectory, a clinician may address potential feelings in the parents of the child's vulnerability and the parents' responsibility. In this regard, she may prefer to elaborate a 'profile' or 'clinical case formulation' of the child including both stronger and more vulnerable characteristics of the child and his context -in combination with or instead of a categorical diagnosis of ASD (Jacobs et al, 2019;Macneil, Hasty, Conus, & Berk, 2012). Throughout this clinical trajectory, we argue against the partition of the diagnostic and the therapeutic phases, as is the case in Flanders -and in many other regions and countries.…”
Section: Discussionmentioning
confidence: 97%
“…Several strategies were employed to strengthen the trustworthiness of the findings (Shenton, 2004). For example, the analytic process was subjected to peer scrutiny by researchers from the local psychology and pedagogy faculties during several meetings and seminars; the data were triangulated by also interviewing physicians working with the same group of children -and their parents-with a similar research question Jacobs et al, , 2019; and, by conducting several interviews, the study's credibility was increased because of its improved potential to generate data which fitted the views of the participants and properly represented the dynamic process (Barbour, 2001;Carter, Bryant-Lukosius, DiCenso, Blythe, & Neville, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The longitudinal evolution from T1 to T2 to T3 is described in another article [39] which addresses the understanding and experiences of ASD throughout time by the included Flemish parents. This longitudinal study in turn is part of a broader research project which triangulates this study's findings by investigating doctors' understanding and clinical experiences of an ASD diagnosis [40][41][42][43].…”
Section: Introductionmentioning
confidence: 95%